La carnitina como suplemento nutricional (Revista Educación Física Chile, 2022)
The objective of this review was to describe the effects and mechanisms of action of carnitine in both humans with special needs and susceptibleto carnitine deficiency, as in athletes and nonathletes. Considering that L-carnitine, as a quaternary amine, its main function is the generation of energy by the cell, acts as transfer reactions of free fatty acids, facilitating the oxidation and energy generation, and supplementation can improvevarious conditions clinics, increase athletic performance and the quality and life expectancy.
Keywords: Carnitine, Supplementation, Health.